Humor Language Representation at Stand-Up Comedy Shows on Metro TV - Surya Kelana Putra; Eddy Setia; Syahron Lubis; Gustianingsih Gustianingsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the humor language representation of Raditya Dhika on the Stand-Up Comedy (SUC) program on Metro TV by using descriptive qualitative research. The data in this study were taken from the monolog Raditya Dhika on the SUC program on Metro TV. Data collection is done by indirect observation techniques. The results showed that Raditya Dhika in his speech acts of humor represented three elements of antics, namely: 1. Locution 2. Illocution and 3. Perlocution. Locution represents the element of antics with the words of blessing, praying, and demanding with no tendency at all. Illocution represents the element of antics with the words and sentences that give permission that have a tendency in speech acts for example, thank you, offer, ask, and promise with the tendency of the partners’ response such as laughter, applause, and screams that arise. Perlocution represents the element of antics through sentences that are deceptive, confusing, encouraging, convincing, encouraging, influencing, embarrassing, and attracting attention and influence from the speech partner such as trying to guess what thought Raditya Dhika will say.